Liposome-Permeability Templating of Gadolinium Hydroxide Nanostructures - Municoy, Sofia (2016)
With the growing attention in building novel nanostructures, there is a need for general approaches to controlling the sizes and shapes in precipitation processes. Here, precipitated gadolinium hydroxides (Gd(OH)3) were made in the form of hollow spheres by control of the liposome permeability. Addition of Gd(NO3)3 to the acidic solution containing the liposomes entrapping OH− creates a self-precipitating template in the precipitation process. The control-formation of these nanostructures takes place through a liposome-membrane phase change. Hybrid nanocapsules are obtained when entrapped hydroxyl ions (OH−) permeates from the liposome and shell material precipitates by forming Gd(OH)3. The morphology of the final product is molded on the original liposome. This synthesis strategy might have implications in significant applications, such as drug delivery systems, and in mineralization, where many processes are also membrane-assisted.